2015
DOI: 10.3390/ma8105349
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Emissivity Coatings to Delay Ignition of Polyethylene

Abstract: Semi-opaque to opaque films containing small amounts of various aluminium particles to decrease emissivity were easily prepared and coated onto low-density polyethylene (LDPE) sheets. The thermal-radiative properties (reflectivity, transmissivity and absorptivity) of the films were measured and related to the aluminum particles’ content, size and nature. Time-to-ignition of samples was assessed using a cone calorimeter at different heat flux values (35, 50 and 75 kW/m2). The coatings allowed significant igniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We attached a 100 μm thick polypropylene film spray coated with a black coating on the top of the amplification chamber with UV-curable adhesive. Black coatings are well known for having the highest emissivity for IR measurement, which is ~1 [10]. The micro-thinned polypropylene film with the black coating guarantees reliable heat transfer from the chamber to the outside and thus makes the temperature measurement possible by an infrared thermometer with high fidelity even from the outside.…”
Section: Methodsmentioning
confidence: 99%
“…We attached a 100 μm thick polypropylene film spray coated with a black coating on the top of the amplification chamber with UV-curable adhesive. Black coatings are well known for having the highest emissivity for IR measurement, which is ~1 [10]. The micro-thinned polypropylene film with the black coating guarantees reliable heat transfer from the chamber to the outside and thus makes the temperature measurement possible by an infrared thermometer with high fidelity even from the outside.…”
Section: Methodsmentioning
confidence: 99%
“…The emissivity coefficient "ε" gives the radiation of heat from various materials as compared with the radiation of heat from an ideal black surface as ε = 1 [16]. The thermal radiative properties of films depend on the content, size and nature of aluminum particles [19]. For anodized aluminum, ε = 0.55 [20].…”
Section: Infrared (Ir) Radiationmentioning
confidence: 99%
“…For anodized aluminum, ε = 0.55 [20]. With increasing concentrations of aluminum, Sonnier et al observed an increase in R, making it a suitable product for limiting thermal radiation from a body [19], whereas for a thin polyethylene terephthalate sheet T = 1.5, for an aluminum-coated foil T can be expected to be less than 1% [20,21]. E and R are complementary, as radiometric measurements mostly depend on surface E and R of radiation [20].…”
Section: Infrared (Ir) Radiationmentioning
confidence: 99%
“…Experiments on transparent conductive oxides on PMMA and thermochromic materials on steel and glass , were then reported but without reaching the low emissivity obtained with copper. Sonnier et al have proposed polyethylene composite coatings filled with aluminum flakes; however, in their case, the top layer was thicker (from 65 to 100 μm), which might not be necessary to reach low emissivity and may limit its impact by introducing more flammable material . From then on, the concept has remained unexploited.…”
Section: Introductionmentioning
confidence: 99%
“…Sonnier et al have proposed polyethylene composite coatings filled with aluminum flakes; however, in their case, the top layer was thicker (from 65 to 100 μm), which might not be necessary to reach low emissivity and may limit its impact by introducing more flammable material. 39 From then on, the concept has remained unexploited. In particular, their main default was not addressed.…”
Section: ■ Introductionmentioning
confidence: 99%